THE INFLUENCE OF ADVERTISING ON REPURCHASE INTENTION OF LUWAK WHITE KOFFIE PRODUCTS AMONG CONSUMERS AMONG LP3I MEDAN POLYTECHNIC STUDENTS - Maulidina Maulidina (Adisam Publisher, 2024)
Repurchase interest is purchase interest that is based on previous purchasing experiences. Advertising is a form of personal or paid communication about an organization, goods, services, or ideas by a known social media or company. This research aims to determine